GÊTHINI : SAJIAN MRABOT DAN KAJIAN GARAP SINDHÈN - Sri Wahyuni; Ananto Sabdo Aji (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
This research examines the work on sindhenan gendhing Gêthini kethuk kalih kerep minggah sekawan laras slendro pathet sanga and its seies, namely work on mrabot with innovations on sindhenan style Surakarta. In working on musicality in the world of karawitan, the author uses concepts namely the mungguh concept by Bambang Sosodoro, the mandheg concept by Ananto Sabdo aji and the concept worked on by Rahayu Supanggah. The method used is qualitative by way of studying book literature or making observations directly or indirectly in order to broaden knowledge to obtain the history of gending and work on musical performances. As well as need interviews with karawitan experts as inputs, ideas and suggestions for conducting this research. The innovations for working on sindhenan lies in the merong kenong parts one and two in balungan seleh ro can be worked on minir pasren, the ngelik kenong two seleh nem part are also worked on minir, because there are balungan melodies that minir can work on. Innovations made by sindhenan on the inggah section can also be worked on by mandheg on the first kenong seleh ji andegan kinanthi and the second kenong seleh nem mandheg andhegan kacaryan, on kenong lu mandheg you can add amdhegan sekar tengahan bawaraga, that’s where sinden has different variations of andegan and gets innovative ideas work on adding a distraction, because in this innovation work on sindhen can show its potential and expertise when the piece is presented.